2019
DOI: 10.1038/s41598-019-53127-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the interplay between human mobility and mosquito borne diseases in urban environments

Abstract: Urbanization drives the epidemiology of infectious diseases to many threats and new challenges. In this research, we study the interplay between human mobility and dengue outbreaks in the complex urban environment of the city-state of Singapore. We integrate both stylized and mobile phone data-driven mobility patterns in an agent-based transmission model in which humans and mosquitoes are represented as agents that go through the epidemic states of dengue. We monitor with numerical simulations the system-level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 46 publications
1
41
0
Order By: Relevance
“…Zhou and Xu [13] used mobile phone sightings data to examine the potential effects of intra-city mobility restrictions on the spread of COVID-19 in the city of Shenzhen. Massaro and Kondor [14] studied the interaction between human mobility and outbreaks of infectious diseases and found that intra-city human mobility is a major factor in the spread of infectious diseases in Singapore. Some studies have analyzed the spatiotemporal pattern of COIVD-19 at the national or district levels [1,15,16].…”
Section: Human Mobility and Infectious Diseasesmentioning
confidence: 99%
“…Zhou and Xu [13] used mobile phone sightings data to examine the potential effects of intra-city mobility restrictions on the spread of COVID-19 in the city of Shenzhen. Massaro and Kondor [14] studied the interaction between human mobility and outbreaks of infectious diseases and found that intra-city human mobility is a major factor in the spread of infectious diseases in Singapore. Some studies have analyzed the spatiotemporal pattern of COIVD-19 at the national or district levels [1,15,16].…”
Section: Human Mobility and Infectious Diseasesmentioning
confidence: 99%
“…An earlier study by ( Massaro et al., 2019 ) used mobile phone data to trace the spread of dengue virus in Singapore during 2013 and 2014 with details of short distances and periods. Therefore, overlaying GIS on IoT mobile data from any infected patient may lead to two things: assist epidemiologists in their search for patient zero, and help identify anyone who has had contact with an infected patient(s) and is at a high risk of being infected.…”
Section: Iomt Application and Technology For Covid-19mentioning
confidence: 99%
“…This mobile phone service showed a strong performance in terms of predictive values, identifying areas with high transmission risk of dengue [86]. Its use has also allowed to create mathematical models based on population movement to predict the spread of disease epidemics [85].…”
Section: Sms Also Demonstrated Good Performance In Terms Of Completenmentioning
confidence: 99%